Emerging Roles of Osteoclasts in the Modulation of Bone Microenvironment and Immune Suppression in Multiple Myeloma - Mansour, Anna; Wakkach, Abdelilah; Blin-Wakkach, Claudine (Frontiers in Immunology, 2017)
Multiple myeloma (MM) is the one of most common form of hematologic malignancy resulting from cancerous proliferation of mature malignant plasma cells (MPCs). But despite the real improve therapeutics in the past years, it remains largely incurable. MM is the most frequent cancer to involve bone due to the stimulation of osteoclast differentiation and activity. Osteoclasts have a unique capacity to resorb bone. However, recent studies reveal that they are not restrained to this sole function. They participate to the control of angiogenesis, medullary niches, and immune responses, including in MM. Therefore, therapeutic approaches targeting OCLs probably affect not only bone resorption but many other functions and OCLs should not be considered anymore only as targets to improve the bone phenotype but also to modulate bone microenvironment. In this review, we explore these novel contributions of OCLs to MM that reveal their strong implication in the MM physiopathology. We also underline the therapeutic interest of targeting OCLs not only to overcome bone lesions, but also to improve bone microenvironment and anti-tumoral immune responses.